Family Property Law: A Comparative Case Study between Lao PDR and Thailand - Vilayphone , Khamphiou; Pisolyabutratovisetkul , Chitaporn; Saengnil , Daranee (Journal of Politics and Governance, 2025)
Societies continually experience conflict over property, specifically marriage property, which sometimes arises through apparent hypocrisy in property law. Disputing spouses and their legal representatives constantly seek to manipulate an interpretation or loophole of law to exploit others out of land or material gain through other financial/status advantages. Many property conflicts, specifically those among married couples of various countries, often present within courtroom auspices in family law. The purpose of this study was to compare the civil code of family law between The People’s Democratic Republic of Lao and Thailand - specifically, property division between husband and wife after separation. Underpinned by the theory of natural rights the qualitative findings support recommendations to reduce conflicts before they reach a court. Specifically, the study examined the two nations' family law history, concepts, and theories related to property division between a husband and wife. The qualitative research approach utilized secondary source documents and literature to inform the comparative content analysis. The findings confirm the historical linkage between Thai and Laos traditions of property ownership, resulting in their many legal similarities. The origins of family law have been passed down from generation to generation, evolving into the contemporary practices of each nation-state. Although both countries broadly adhere to ‘property ownership principles’ for dividing property between a husband and wife, they differ in how each State deems property pre- and post-marriage. In both countries, property owned by an individual pre-marriage and that willed or bequeathed to such individual during the marriage is categorized as “original” property (initial property or Sing Suan Tua). In contrast, marital property (Sin Som Sang) is co-jointly amassed during the marriage. Here, however, the bilateral similarity stops. While Thai family law retains the founding principle of property ownership rights, Lao Family Law, Section 168, stipulates that the “original property” becomes “marital property” whenever such original property is renovated exceeding a value two-thirds of the original value, specifically using assets of the other spouse. This distinct deviation in Lao Family Law from the founding principle of property ownership appears soon after the explosion of the French Protectorate of Laos 1893-1975. This provision, however, seemingly promotes less equity among the disputing parties in Lao, acting as an injustice to the owner of the original property. The findings support a recommendation that Section 168 of the Lao Family Law Act be repealed (specifically, paragraph 3, which conflicts with ownership theory) to be replaced by Lao “customary principles of property ownership”, aligning with neighboring Thailand's “equity property rights”.